Sustainable Performance of Rural Banks (BPRs) in Buleleng Regency: A Balanced Scorecard Perspective - Putu Riesty Masdiantini; Sunitha Devi (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
This study examines the sustainable performance of Rural Banks (Bank Perkreditan Rakyat-BPRs) in Buleleng Regency after the COVID-19 pandemic using the Balanced Scorecard (BSC) framework. As microfinance institutions that play a vital role in empowering low-income communities, BPRs are currently facing major challenges, including consolidation pressures, competition with commercial banks, and the need to improve internal efficiency. The main objective of this study is to analyze the influence of the four BSC perspectives financial, customer, internal business process, and learning and growth on the sustainable performance of BPRs. The research adopts an associative quantitative approach using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The population consists of eight active BPRs in Buleleng Regency, involving 60 valid respondents comprising managers, accounting heads, and structural officers. Data were collected through structured questionnaires based on BSC indicators measured using a five-point Likert scale, and analyzed with SmartPLS to test the relationships and the strength of influence among variables. The results reveal that the financial perspective and learning and growth perspectives have significant positive effects on sustainable performance, while the customer and internal business process perspectives show no significant effect. These findings reinforce the Resource-Based View (RBV) theory by highlighting that strengthening internal resources particularly financial governance, employee competence, innovation capability is crucial for achieving institutional sustainability in a dynamic business environment.